(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
In the structure of tectonic magnetic field the component of its active dynamic part is found, which is called as dynamic tectonic magnetic field (DTM). The possible functional connection between the parameters of DTM and parameters of earthquake sources are investigated. As a result a constant quantity is obtained connecting these parameters.